Platelet count to spleen thickness ratio is related to histologic severity of primary biliary cholangitis. Issue 7 (February 2018) - Wang, Zhongfeng; Liu, Xu; Xu, Hongqin; Qu, Limei; Zhang, Dezhi; Gao, Pujun
Abstract : Abstract: The aim of this study was to evaluate the ability of noninvasive markers to identify the histological severity of primary biliary cholangitis (PBC). Fifty-eight treatment-naïve PBC patients who had undergone liver biopsy were enrolled in our study. The patients' histological stages were based on the classifications of Ludwig and Scheuer. Aspartate aminotransferase-to-platelet ratio index (APRI), fibrosis index based on the 4 factors (FIB-4), red blood cell distribution width to platelet ratio (RPR), and platelet count to spleen thickness (PC/ST) ratio were calculated. Using the area under the receiver operating characteristic curve (AUROC) to evaluate the accuracy of different markers for predicting the histological severity. Among the 58 treatment-naïve PBC patients, the patients of Scheuer stage I/II/III/IV were 17/25/11/5, respectively. PC/ST ratio (AUROC = 0.807) was superior to RPR (AUROC = 0.717), APRI (AUROC = 0.726), FIB-4 (AUROC = 0.722), and mean platelet volume (MPV) (AUROC = 0.671) in discriminating between stage I and stage ≥II. The AUROC of PC/ST ratio, RPR, APRI, FIB-4, and MPV were 0.939, 0.872, 0.816, 0.831 and 0.572, respectively, for Scheuer stage ≥III; 0.968, 0.795, 0.744, and 0.723, respectively for stage IV. The sensitivity and specificity of PC/ST ratio were 73.4%, 79.1%; 81%, 100%;88.7%, 100% for detection of Scheuer stage ≥ II, Scheuer stage ≥ III and Scheuer stage IV, respectively. Our study findings indicated that compared with previous noninvasive test PRP, APRI, FIB-4 and MPV, PC/ST ratio shows the most accurate for distinguish the histologic severity of PBC patients.